Prevalence of tobacco use among cancer patients in Iran: a systematic review and meta-analysis - Mohammad Moein Vakilzadeh; Reza Khayami; Danyal Daneshdoust; Reza Moshfeghinia; Farzad Sharifnezhad; Zahra Taghiabadi; Hanieh Keikhay Moghadam; Mohammad Ali Karimi; Atousa Ghorbani; Pegah Bahrami Taqanaki; Nima Boojar; Adele Azarshab; et al. (BMC, 2024)
Abstract Background The prevalence of tobacco use among various cancer types in Iran remains a significant concern, necessitating a comprehensive analysis to understand the extent and patterns of consumption. This study aimed to systematically review and analyze existing literature to delineate the prevalence of tobacco use across different cancer types in Iran, thereby providing a robust basis for future interventions and policy formulations. Methods Adhering to the PRISMA guidelines, we conducted a systematic review and meta-analysis of literature available in PubMed and Scopus databases. The initial search identified 351 records, out of which 44 studies were selected based on their relevance and design. These studies spanned various time frames, starting from the 2001s up until 2022, and encompassed diverse geographical locations and cancer types in Iran. To avoid bias and potential data overlap, we opted to incorporate a single comprehensive study from the Golestan Cohort, encompassing all data, while excluding 10 other studies. Our final analysis incorporated data from 34 studies, which accounted for 15,425 patients and 5,890 reported smokers. Statistical analyses were performed to calculate the overall proportion of tobacco consumption and to conduct subgroup analyses based on different variables such as cancer types, gender, geographical locations, and types of tobacco used. Results The analysis revealed a substantial prevalence of tobacco use among cancer patients in Iran, with an overall consumption rate of 43%. This rate varied significantly, ranging from 10 to 88% across individual studies. Subgroup analyses further highlighted disparities in tobacco consumption rates across different demographics, geographic areas, and cancer types. Notably, the 'ever' smokers category exhibited the highest prevalence of tobacco use. The study also identified a worrying trend of high cigarette smoking rates, along with variable consumption patterns of other forms of tobacco, including waterpipe, 'Naas', and 'Pipe'. Conclusions This systematic review and meta-analysis underscores a significant association between tobacco consumption and various cancer types in Iran, with a prevalence rate among cancer patients being three times higher than the average Iranian population. The findings indicate substantial heterogeneity in tobacco use patterns, emphasizing the need for targeted interventions to address this pressing health issue. The study serves as a critical resource for shaping future policies and strategies aimed at curbing tobacco use and mitigating its adverse effects on cancer prevalence in Iran.